Legal Analysis on the Policy of Home Ownership Requirements for Foreigners in the Consumer Credit Agremeent of Syariah Bank in Indonesia - Eka Husnul Khotimah, Rachmadani (Mazahib, 2018)
The study examines the normative policy on the ownership rules of residential homes for foreigners in the credit agreement consumption of Syariah banks in Indonesia. This policy has existed since 2005. However, it does not make all Syariah banks in Indonesia provide credit facilities to foreigners since there is no specific implementing regulation and legal protection for the banks in the case of finance arrears caused by the practice which can disrupt their liquidity and profitability. Considering this, the article analyses the legal protection for Islamic banks, both in preventive and repressive context, in providing credit facilities for foreigners, so that they all can facilitate loans without any fears and risks. This becomes necessary as it can contribute to Indonesia’s economic growth.  It argues that the law should cover this matter, through both preventive and restrictive measures, in which the law should prevent the practice from causing finance arrears through musyārakah contract.  The results of this study confirm that there is legal protection that has been regulated by Bank Indonesia for Syariah Bank in giving credit to a foreigner.Keywords: Legal Policy, Syariah Bank, Foreigners, Consumer Credit Agreement